2009
DOI: 10.1002/elps.200800664
|View full text |Cite
|
Sign up to set email alerts
|

A sheathless CE/ESI‐MS interface with an ionophore membrane‐packed electro‐conduction channel

Abstract: A robust and convenient sheathless CE/ESI-MS interface realized with an ionophore membrane-packed electro-conduction channel is described. Sheathless interfaces that may provide higher sensitivity for MS detection than sheath flow-supported interfaces generally show instability and short lifetimes due to their imperfection in making an electrical contact with the emitter tip. In this work, we designed a sheathless interface based on an ionophore membrane-packed electro-conduction channel. At the joining point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In our previous study, we reported that a gap between the two capillaries in the capillary channel could lead to significant peak tailing . In this work, we tightly butted two capillaries to minimize the dead volume and peak tailing introduced by the gap.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, we reported that a gap between the two capillaries in the capillary channel could lead to significant peak tailing . In this work, we tightly butted two capillaries to minimize the dead volume and peak tailing introduced by the gap.…”
Section: Resultsmentioning
confidence: 99%
“…The sheathless CE/ESI‐MS interface was constructed based on the work of Shi et al . The expansion or trimming of fine holes on the interface was manually performed at our laboratory as necessary.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenges of building robust two‐piece sheathless interfaces lie in aligning the separation column end and emitter with minimum gap, and maintaining stable electric contact at the joint of the two pieces. In the design made by Park et al , two ports of a three‐port plastic tee were used to secure the separation column and the emitter, and the third one was packed with Nafion, which formed a conductive polymer layer that allows cations to move through. A piece of sponge soaked with electrolyte was placed on top of the Nafion layer and voltage for electrospray was applied through a platinum wire wrapping around the tee.…”
Section: Online Coupling Of Ce and Esi‐msmentioning
confidence: 99%